A study of effective measures for talent retention in Singapore aerospace maintenance context - Lim, Tabris Wei Jye (2020)
Singapore Aerospace Maintenance Industry (SAMI) contributed to 10 percent of the global output in maintenance, repair, and overhaul (MRO) services. Continuous growth of the global commercial fleet is incurring high demands on aerospace maintenance services. Singapore as world’s leading MRO hub requires skilled, trained, and experience talent pool to ensure the sustainable competitive advantages of SAMI to capture this opportunity.